2005
DOI: 10.17221/5660-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Random amplified polymorphic DNA (RAPD) analysis of Ornithobacterium rhinotracheale strains isolated from chickens in Turkey

Abstract: Six field strains of Ornithobacterium rhinotracheale isolated from chickens in Elazig province located in the East of Turkey were typed by serotyping and random amplified polymorphic DNA assay using a random primer . Using the AGP test used for serotyping, serotype A was found to be the predominant serotype, only one strain was serotyped as serotype B. By RAPD assay, the tested ORT strains were found to have different RAPD profiles. In addition, the RAPD assay showed almost similar DNA profiles among the teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Again, strains RefA, RefB and RefE clustered together in the neighbor-joining tree, and strains RefD and RefH showed close relationship to each other. Likewise, Ozbey et al [ 19 ] found that some strains of serotype A shared their RAPD profile with those of serotype B and E. Only the serotype reference strain C (this study RefC) had a unique RAPD profile. The relationship between strains of serotypes A and B as well as the distinct RAPD profile of serotype C were confirmed by Waldow [ 20 ].…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Again, strains RefA, RefB and RefE clustered together in the neighbor-joining tree, and strains RefD and RefH showed close relationship to each other. Likewise, Ozbey et al [ 19 ] found that some strains of serotype A shared their RAPD profile with those of serotype B and E. Only the serotype reference strain C (this study RefC) had a unique RAPD profile. The relationship between strains of serotypes A and B as well as the distinct RAPD profile of serotype C were confirmed by Waldow [ 20 ].…”
Section: Resultssupporting
confidence: 59%
“…Serotype-specific relationships have been indicated by previous studies using PFGE [ 21 ], 16S rRNA and Or01 [ 15 ] gene analyses or RAPD-PCR [ 19 , 20 ] for characterization of ORT. In the PFGE analysis serotype strains A-Q were identical with RefA-RefQ used in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no correlation with the origin of the isolates was found. Ozbey et al (2005) reported high genetic diversity among O. rhinotracheale isolates from chickens in Turkey with an RAPD assay using the OPG11 primer. However, they used only six field isolates, which represented six different profiles, so the number of isolates was too low to draw such farreaching conclusions.…”
Section: Discussionmentioning
confidence: 99%